Keberadaan Seni Gejog Lesung Mukti Lestari di Desa Pendowoharjo Bantul Yogyakarta - Supriyadi Supriyadi (SELONDING, 2017)
Art evolves with the dynamics of society. The reflection of the geographical region through the form of an art is a picture that a form of art can not be separated from the elements of life and nature that surrounds the community. In agrarian society in Krandohan Pendowoharjo Sewon Bantul village, the community is close to an art form that is characterized by agrarian art of Gejog Lesung. Art is well developed in the area because the people still put Gejog Lesung as a form of entertainment performances. Along with the development of a dynamic era, then Gejog Lesung decadence in continuity. On the one hand the generation of mothers who are getting older as main supporters of Gejog Lesung art feel not as energetic as before in his appearance. On the other hand the younger generation are reluctant to learn and engage in art activities Gejog Lesung. Such problems often occur in the existence of a traditional performing arts. Feminism in the show Gejog Lesung with the role of mothers, making the art has its own specifications, given the busyness owned by most of the mothers either as housewives or other workers still take the time to engage in such activities. The degrading view of the potential possessed by a woman can be avoided by seeing the activities of these mothers. Etnomusikologis a form of art can be seen a manifestation in the system contained in a society. Through the art Gejog Lesung can be seen from the pattern of a form of society in appreciating the arts.